Latin Woman Potentate of the Roman Empire: Reign of Yolanda of Flanders - Valentine J. Belfiglio (Research Aspects in Arts and Social Studies Vol. 8, 2023)
The main goal of this essay is to develop a personality profile of Yolan- da, an Eastern Roman Empire Latina potentate. The main issue the author is trying to address is whether or not Yolanda’s personality can be used as a model for the characteristics of contemporary women in politics. The most important information in this article is the influence of family, religion, schooling, class, status, experiences, and social contacts upon the psychological development of Yolanda. The findings of this study challenge the theory that constructivism or gender determines the role of women within a political system. The collective experiences of Empresses Irene, Zoe, Theodora and Yolanda suggest that class and political connections are more important than social construction and gender in determining the rise of women to high political office.